A Closed Metallomolecular Cage that can Open its Aperture by Disulfide Exchange. Issue 6 (2nd January 2019) - Akine, Shigehisa; Miyashita, Masato; Nabeshima, Tatsuya
Abstract: A closed metallomolecular cage based on the tris(saloph) framework, in which its aperture can be opened by disulfide exchange, was designed. At the apertures of the molecular cage, bridging diamine ligands having a disulfide bond were introduced to close the cage structure. These bridging ligands efficiently blocked the uptake of a guest, Cs +, but the presence of a thiolate anion significantly accelerated the guest uptake. This clearly means that this cage complex became open by the addition of the thiolate anion, because the cage closure becomes more dynamic due to the disulfide exchange reaction. Abstract : A closed metallomolecular cage based on the tris(saloph) framework, in which its aperture can be opened by disulfide exchange, was designed. At the apertures of the molecular cage, bridging diamine ligands having a disulfide bond were introduced to close the cage structure. These bridging ligands efficiently blocked the uptake of a guest, Cs +, but the presence of a thiolate anion significantly accelerated the guest uptake.